Pengembangan Sistem E-Zakat Berbasis Web dengan Metode Feature-Driven Development pada Baznas Kabupaten Tulungagung (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Manual zakat management at BAZNAS Tulungagung Regency still faces various obstacles, such as data recording errors, delays in report preparation, and less than optimal transparency of zakat fund distribution information. This study aims to design, develop, and evaluate a web-based E-Zakat System that suits the operational needs of BAZNAS Tulungagung Regency. The study uses a Research and Development (R&D) approach with data collection through observation and interviews with BAZNAS managers to identify system requirements. The software development process applies the Feature-Driven Development (FDD) method which includes five stages, namely Develop an Overall Model, Build a Feature List, Plan by Feature, Design by Feature, and Build by Feature. The system was developed using the Laravel Livewire 3 framework with a MySQL database, and is equipped with features for managing muzakki and mustahiq data, zakat payments and distribution, content management, WhatsApp notifications, and user management. System evaluation was carried out using Black Box Testing. The test results showed that all 47 test scenarios were successfully executed according to their functions, so that the system was declared suitable for use to support more effective, efficient, transparent and accountable zakat management.